A Comparison of the Influence of Temperature During Slurry and Gas Phase Propylene Polymerization on Ziegler‐Natta Catalyst. Issue 1 (23rd December 2016) - Cancelas, Aarón J.; Hongmanee, Goond; Andrade, Fabiana N.; Terano, Minoru; Taniike, Toshiaki; McKenna, Timothy F.L.
Summary: Semi‐batch propylene polymerizations were performed in slurry and gas phase using a supported Ziegler‐Natta catalyst. The obtained instantaneous reaction rates were fitted with a kinetic model, and the influence of bulk temperature and reaction phase on kinetic parameters was studied. The estimated propagation constant increased with increasing reaction temperature up to 90 °C in slurry phase polymerizations, but reached a maximum at 60 °C when propylene was polymerized in the gas phase. Gas phase stopped flow reactions were done at 60 and 70 °C to investigate the strong influence of temperature during the initial instants of reaction and to evidence thermal degradation at particle level. These results and those from autoclave reactor were well consistent and could explain the effects of temperature.